Strategies to induce broadly protective antibody responses to viral glycoproteins - F Krammer (Taylor & Francis Group, 2017)
Introduction: Currently, several universal/broadly protective influenza virus vaccine candidates are under development. Many of these vaccines are based on strategies to induce protective antibody responses against the surface glycoproteins of antigenically and genetically diverse influenza viruses. These strategies might also be applicable to surface glycoproteins of a broad range of other important viral pathogens. Areas covered: Common strategies include sequential vaccination with divergent antigens, multivalent approaches, vaccination with glycan-modified antigens, vaccination with minimal antigens and vaccination with antigens that have centralized/optimized sequences. Here we review these strategies and the underlying concepts. Furthermore, challenges, feasibility and applicability to other viral pathogens are discussed. Expert commentary: Several broadly protective/universal influenza virus vaccine strategies will be tested in humans in the coming years. If successful in terms of safety and immunological readouts, they will move forward into efficacy trials. In the meantime, successful vaccine strategies might also be applied to other antigenically diverse viruses of concern.